STRATEGI KOMUNIKASI PEMASARAN WEDRINK SOLOBARU MELALUI MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN KEPUASAN KONSUMEN - Kinasih, Sekar; Itasari, Andri Astuti; Herawati, Dewi Maria (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
ABSTRACT The marketing communication strategy (promotion) is crucial for achieving company goals. Wedrink Solobaru, as a new food and beverage franchise, competes with other brands like Mixue and Momoyo in Solo City. Every business player has strategies to attract and enhance customer satisfaction. Despite being new, Wedrink Solobaru has shown rapid growth with an increasing number of visitors. This study aims to describe the marketing communication strategy of Wedrink Solobaru through Instagram in improving customer satisfaction. This research is descriptive qualitative, using primary data from interviews and observations, as well as secondary data from documents, books, and journals. Data collection techniques involve purposive sampling, with credibility tested through triangulation. Analysis is conducted using the Miles and Huberman method, including data collection, reduction, presentation, and conclusion drawing. The study results indicate that the marketing communication strategy of Wedrink Solobaru, through the 4P marketing mix and marketing communication mix, has successfully improved customer satisfaction. However, in terms of advertising, the mismatch between the received products and the advertising content still causes dissatisfaction. Keywords: Marketing Communication Strategy, Instagram, Customer, Satisfaction